The benefits of children’s shared musical activities in the home to their later formal learning - Blackburn, Carolyn (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
This paper reports on a study that explores the benefits of young children’s shared musical activities in the home to their later learning. Existing literature has been strengthened with family interviews to explore current trends in family practices relating to young children’s musical experiences. The findings suggest that there are benefits to children’s pro-social and physical development from participating in shared musical activities, and there are also there are benefits to relationships in families. In contrast to previous studies, participants in this study reported that children engage in musical activities every day in the home. However, they also participate in organised musical activities outside the home. Further research into the nature and quality of organised musical activities outside the home is needed.
Keywords: curriculum; family; music; parents; relational pedagogy